1971
DOI: 10.1073/pnas.68.4.866
|View full text |Cite
|
Sign up to set email alerts
|

Sequences of Pituitary and Placental Lactogenic and Growth Hormones: Evolution from a Primordial Peptide by Gene Reduplication

Abstract: Human placental lactogen has been found to resemble human pituitary growth hormone very closely in amino acid sequence, about 80% of the residues examined being identical in the two molecules when a revised sequence for growth hormone is used as the basis for comparison. The structural features responsible for the differing biological potency of the two hormones may therefore reside in rather limited regions of primary structure. The observation of internal sequence homologies within the pituitary growth hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
3

Year Published

1972
1972
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(81 citation statements)
references
References 16 publications
2
74
0
3
Order By: Relevance
“…PRL is a polypeptide hormone, which is secreted in a pulsatile fashion and is structurally related to GH and human placental lactogen (hPL) (Niall et al, 1971). PRL release follows a circadian rhythm, with increased secretion in the early evening hours (Sassin et al, 1972;Waldstreicher et al, 1996).…”
Section: Prolactin's Physiologic Rolementioning
confidence: 99%
“…PRL is a polypeptide hormone, which is secreted in a pulsatile fashion and is structurally related to GH and human placental lactogen (hPL) (Niall et al, 1971). PRL release follows a circadian rhythm, with increased secretion in the early evening hours (Sassin et al, 1972;Waldstreicher et al, 1996).…”
Section: Prolactin's Physiologic Rolementioning
confidence: 99%
“…The sequences of growth hormones and prolactins show some homology [13,17,19,20] and indicate that the two hormones can be considered members of a single family of protein hormones. This is clear when the sequences of bovine growth hormone [ 111 and bovine prolactin ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prolactin is also homologous with human placental lactogen [ 13,17,19,20] but the degree of homology between these two lactogenic hormones is no greater than that between prolactin and growth hormone, while human placental lactogen and human growth hormone show a high degree of homology.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent investigation of their amino-acid composition showed close similarities (Friesen, 1965;Catt et al, 1967;Sherwood, 1967). Recently Niall et al (1971) have succeeded in establishing much of the amino-acid sequence of HCS and showed that there is an identity of more than 80% between the molecules of HCS and HGH. Sherwood et al (1971) and Li et al (1971) have achieved a complete identification of the structure of HCS which they find to contain 190 amino-acid residues, the same number as in HGH, and also found 85% of residues to be identically placed in the two molecules.…”
Section: S T R U C T U R Ementioning
confidence: 99%